2017
DOI: 10.1038/ng.3963
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer connectome in primary human cells identifies target genes of disease-associated DNA elements

Abstract: The challenge of linking intergenic mutations to target genes has limited molecular understanding of human diseases. Here we show that H3K27ac HiChIP generates high-resolution contact maps of active enhancers and target genes in rare primary human T cell subtypes and coronary artery smooth muscle cells. Differentiation of naive T cells into T helper 17 cells or regulatory T cells creates subtype-specific enhancer–promoter interactions, specifically at regions of shared DNA accessibility. These data provide a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
508
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 461 publications
(564 citation statements)
references
References 60 publications
36
508
1
1
Order By: Relevance
“…Our analyses support that BMI1 is the gene target of an enhancer element ~180Kb upstream containing SNP rs11591377, with data from recent H3K27ac HiChIP experiments 21 , as well as MethylC-seq patterns of CpG methylation across tissues, suggesting this enhancer is specific to HSCs and early B-cell progenitors. Enhancers are often tissue or cell-type specific (reviewed in Heinz et al .…”
Section: Discussionsupporting
confidence: 84%
“…Our analyses support that BMI1 is the gene target of an enhancer element ~180Kb upstream containing SNP rs11591377, with data from recent H3K27ac HiChIP experiments 21 , as well as MethylC-seq patterns of CpG methylation across tissues, suggesting this enhancer is specific to HSCs and early B-cell progenitors. Enhancers are often tissue or cell-type specific (reviewed in Heinz et al .…”
Section: Discussionsupporting
confidence: 84%
“…Our data suggest that the risk haplotype may contain SNPs that alter the function of enhancers that increase ANRIL expression (compared to the non-risk haplotype) because deleting the risk (but not non-risk) haplotype (ANRIL exons 10-19) reduces expression of the remaining upstream ANRIL exons (1-9) (Figure 5). Intriguingly, a recent paper examining long-range chromatin interactions showed that non-coding candidate regulatory regions within the 9p21.3 risk haplotype associated more strongly with the ANRIL enhancer (and also with the nearby CDKN2B enhancer) compared to the analogous region in the non-risk haplotype (Mumbach et al, 2017). This mechanism could explain at least part of the phenotype we observe, since we can mimic several key cellular and molecular phenotypes in NN KO cells via ANRIL overexpression.…”
Section: Discussionmentioning
confidence: 96%
“…Understanding the complex biological underpinnings of human disease has long been a goal of network biologists (Barabási & Oltvai, ; Barabási et al , ). Because genes vary in their role and importance across diverse cell types, it has become increasingly clear that characterizing tissue‐ and cell type‐specific regulation of chromatin accessibility (Roadmap Epigenomics Consortium et al , ; Breeze et al , ), chromosome looping (Javierre et al , ; Mumbach et al , ), and gene expression (GTEx Consortium et al , ) will be central to developing a coherent understanding of disease etiology. Differences in biological pathway importance across tissues are especially vexing when modeling diseases such as cancer that specifically exploit tissue‐specific pathways and preferentially acquire mutations to regulate them.…”
Section: Introductionmentioning
confidence: 99%